Development and psychometric evaluation of a questionnaire to measure university students’ knowledge on the effects of alcohol use during pregnancy - Leite, Guilherme Petek Ramos; de Avó, Lucimar Retto da Silva; Germano, Carla Maria Ramos; Melo, Débora Gusmão (Frontiers in Public Health, 2024)
Introduction: Alcohol consumption during pregnancy can lead to fetal alcohol spectrum disorders. This study developed and validated a questionnaire to assess university students' knowledge regarding the effects of alcohol during pregnancy.We designed an instrument with true-false-I don't know statements. Initially, 45 true statements were formulated and subjected to content validation by 19 experts. Based on the Content Validity Index (CVI), 17 items were selected. The instrument, called the Fetal Alcohol Consequences Test (FACT), was first assessed by 31 university students for the level of understanding. Then, the questionnaire was administered to a national Brazilian sample of university students, and an Exploratory Factor Analysis (EFA) was conducted. Each correct FACT answer was worth 1 point, and the knowledge was categorized as high (total score ≥ 80%), moderate (score between 60-79%), and low (score ≤ 59%). Results: When the questionnaire was being designed, the CVI values ranged from 0.779 to 1.0, and all statements were considered suitable by the target audience. For psychometric evaluation, 768 students from 24 Brazilian states participated. In the EFA, five statements were removed, revealing a tool with 12 items and two latent factors: "fetal alcohol spectrum disorders" and "conceptions and guidance on alcohol consumption during pregnancy". The KMO index (0.76426) and Bartlett's sphericity test (6362.6, df = 66, p < 0.00001) both supported the final EFA model. The goodness-offit indices for the factor structure were adequate: χ2 = 119.609, df = 43, p < 0.00001; RMSEA = 0.048; CFI = 0.977; TLI = 0.965. The mean total FACT score among participants was 7.71±2.98, with a median of 8; 32.03% of the students had high (10-12 points), 24.09% moderate (8-9 points), and 43.88% low knowledge (< 8 points). The questionnaire proved reliable, with a floor effect of 1.17%, a ceiling effect of 9.25%, and a Cronbach's alpha index of 0.798.The FACT can be utilized in university students' health education processes, contributing to greater knowledge and information dissemination about the effects of alcohol during pregnancy, in addition to the formulation of policies on the subject directed to this group of young adults.